IMPLEMENTASI PROGRAM PENDIDIKAN KEWIRAUSAHAAN (PKW) DALAM MENINGKATKAN MINAT WIRAUSAHA MASYARAKAT DI PKBM DORIT TUNGAL - Paskalita, Lidwina Apriani; Achmadi, Achmadi; Kuswanti, Heni (Universitas Tanjungpura, 2025)
The study aims to determine the implementation of entrepreneurship education programs in increasing community entrepreneurial interest in PKBM Dorit Tungal. This study uses a qualitative approach with a case study method. The informants in this study numbered 8 people with data collection techniques in the form of interviews, observations and documentation. The data analysis technique used was data reduction, data presentation and drawing conclusions. Testing the validity of the data using triangulation techniques and sources. The results of this study indicate that this entrepreneurship education program has succeeded in increasing community entrepreneurial interest as indicated by participants who experienced an increase in both knowledge and skills. The most obvious increase occurred in self-confidence, the ability to take risks and the ability to manage time. The balanced learning method between theory and practice has proven effective. Participants feel they understand entrepreneurship material better through direct practice. Participants begin to understand the importance of planning, marketing and management in entrepreneurship. Participants begin to realize the importance of communication and decision making in a team. Participants also show the courage to innovate and adapt to the market and begin to pay attention to factors that influence business sustainability in the future.